HAT: a high‐energy surface X‐ray diffraction analysis toolkit. Issue 1 (31st January 2023) - Harlow, Gary S.; Pfaff, Sebastian; Abbondanza, Giuseppe; Hegedüs, Zoltan; Lienert, Ulrich; Lundgren, Edvin
Abstract : Computer software for the analysis and extraction of high‐energy surface X‐ray diffraction data is presented. Abstract : This work introduces the high‐energy surface X‐ray diffraction analysis toolkit ( HAT ), an open‐source cross‐platform software package written in Python to allow the extraction and processing of high‐energy surface X‐ray diffraction (HESXRD) data sets. Thousands of large‐area detector images are collected in a single HESXRD scan, corresponding to billions of pixels and hence reciprocal space positions. HAT is an optimized reciprocal space binner that implements a graphical user interface to allow the easy and interactive exploration of HESXRD data sets. Regions of reciprocal space can be selected with movable and resizable masks in multiple views and are projected onto different axes to allow the creation of reciprocal space maps and the extraction of crystal truncation rods. Current and future versions of HAT can be downloaded and used free of charge.